Palmoplantar Psoriasis: Treatment with Calcipotriol and Local UVA Radiation Compared with Local PUVA - Tsankov, Nikolai; Meymandi, Simin; Grozdev, Ivan; Shafiei, Hamidreza (Journal of Lasers in Medical Sciences, 2011)
INTRODUCTION: Palmoplantar psoriasis could hardly be differentiated from chronic tylotic eczema both clinically and histologically. The most commonly used therapeutic options for palmoplantar psoriasis are long-term therapy with topical corticosteroids and local PUVA. Frequently, it is a recalcitrant disease. We investigated the efficacy and tolerability of the combination of topical calcipotriol with local UVA radiation in comparison with local PUVA therapy. METHODS: In a total of 43 patients with palmoplantar psoriasis, 33 were given 15 sessions of local UVA radiation and topical calcipotriol and the remainder received 15 sessions of local PUVA (psoralen + UVA radiation). RESULTS: The statistical analyses of the results showed that the effect and tolerability of both therapeutic modalities are comparable. CONCLUSION: Combination of topical calcipotriol and local UVA radiation is an optional corticosteroid-free therapeutic modality for palmoplantar psoriasis. It has a comparable effectiveness and tolerability with local PUVA.